Respiratory function the Korean elite judo athletes and non-athletes - Shin, S.; Yang, M.; Kim, H.; Lee, U. K.; Kim, Y.; Lee, K.; Park, S.; Lee, D.; Noh, W.; Kim, J.; Kwak, Y.; Lee, H.; et al. (Archives of Budo, 2017)
Background and Study Aim: Respiratory function (respiratory system) is important for patients including judo athletes who require sports rehabilitation. The purpose of this study was knowledge about the respiratory function of Korean elite judo athletes and non-athletes.